Penentuan Nilai SPF (Sun Protection Factor) Sediaan Serum Anti-Aging Ekstrak Rimpang Galoba (Horstedtia Alliacceae) - Safaruddin, Safaruddin; Suleman, Abdul Wahid; Zahira, Saliza (Journal of Pharmaceutical and Health Research, 2024)
The rhizome of Galoba (Horstedtia alliacceae) contains flavonoids, alkaloids, saponins, tannins, and triterpenoids which are secondary metabolite compounds that have antioxidant activity. The most antioxidants are flavonoids where antioxidants are used as anti-aging agents because free radicals are involved in the aging process of the skin. Objectives of the study to determine whether ethanol extract of galoba rhizome (Horstedtia alliacceae) can be formulated into a physically and chemically stable serum preparation, as well as to determine the SPF (Sun Protection Factor) value in serum preparations. The research method used an experimental method in vitro using a UV-Vis spectrophotometer, extraction by maceration method using 96% ethanol solvent, and then an anti-aging serum preparation formulation was made with concentrations of F1 (5%), F2 (10%), F3 (15%), F3 (20%). Then the SPF (Sun Protection Factor) value is determined. The results of the serum formula research showed that it was physically and chemically stable, which was marked by no difference before and after the cycling test, both in organoleptic, homogeneity, pH, viscosity, and humidity tests. The results of the SPF value of serum preparations at F1 (5%) were 4.51, F2 (10%) was 5.66, F3 (15%) was 8.67, and F4 (20%) was 13.06. The conclusion of this study is to show that Galoba rhizome extract (Hornstedtia alliacea) can be formulated into a physically and chemically stable anti-aging serum preparation, and the best SPF value obtained from the F4 formula (20%) is 13.06 with the maximum protection category.